Investigating the Polymorphism in PR179: a Combined Crystal Structure Prediction and Metadynamics Study - Zykova-Timan, T.; Raiteri, Paolo; Parrinello, M. (American Chemical Society, 2008)
The polymorphism of an industrial important pigment (PR179) was studied with a combination of standard crystal structure prediction and metadynamics. The former provided a starting set of candidate polymorphs whose structural and thermal stability were then probed by metadynamics. Moreover, metadynamics allowed for exploring the free energy surface to look for other possible polymorphs that were not included in the original set. Our calculations indicate that two structures have a high structural stability and are therefore good candidates to be found in experiments. The lower energy phase of the two indeed corresponds to the known polymorph, and we suggest that the other might be a metastable polymorph not yet experimentally discovered.